Beating the blaze: Fire survival in the fan aloe (Kumara plicatilis), a succulent monocotyledonous tree endemic to the Cape fynbos, South Africa. (28th September 2015) - Cousins, Stephen R.; Witkowski, Ed T. F.; Pfab, Michèle F.
Abstract: Fire is central to the ecology of Mediterranean‐type climate ecosystems, but little is known about the fire ecology of succulent plants therein. This study investigated the fire ecology of an arborescent succulent monocot, K umara plicatilis (L.) G. D. Rowley (Asphodelaceae), a Cape fynbos endemic. Habitat suitability was assessed to determine whether the species tolerates or 'avoids' fire, and fire survival traits (bark thickness and tissue water content) were measured. The population size structure and density of three K . plicatilis populations were assessed after natural fires, and resprouting potential was investigated. K umara plicatilis adopts a dual fire survival strategy, occupying rocky sites to 'avoid' fire and possessing morphological features that afford fire tolerance, e.g. well‐protected apical meristems and thick corky bark. Bark thickness of burned individuals in situ was similar to unburned plants, suggesting that K . plicatilis bark provides effective insulation against fire. Mortality rates were 64%, 40% and 11%, and decreased as rock cover at the population level increased. All three populations showed reduced plant density post‐fire, with greater density reductions associated with lower rock cover. Small plants appear most vulnerable to fire damage due to lower absolute bark thickness and plant heights within the flame zone. K umara plicatilis is an apical sprouter, recovering after fire or mechanical stem damage by onward growth from surviving stem apices, rather than resprouting. Post‐fire population recovery therefore likely depends on inter‐fire recruitment.